COMPOSITE ARMATURES IN CONSTRUCTION PROSPECTS FOR APPLICATION - Ass. Abdullayev U. M. (Journals Park Publishing, 2022)
This article presents the advantages and disadvantages of using composite reinforcement in construction in comparison with traditional steel reinforcement.
Keywords: composite and steel reinforcement, construction, basalt fiber.